Perfil das cirurgias cranio-faciais em um hospital de ensino: estudo prospectivo longitudinal - Pinto, Vanessa Gabriela Gonzales (2018)
Orthognathic surgery is the treatment of choice for the correction of severe dentofacial deformities. It is based on the surgical manipulation of the bones of the face in order to correct anatomical relations, malocclusions and treatment of Sleep Apnea and Hypopnea Syndrome - OSAHS. Objective: The objective of this study was to study the profile of orthognathic surgery of patients who were surgically treated in the otorhinolaryngology department and to analyze whether there was statistical significance by means of logistic regression between the patients' age and the orthognathic surgery profile. Methodology: The present study was based on an observational study with a longitudinal prospective model, with an evaluation of the charts of patients submitted to orthognathic surgeries with statistical and descriptive procedures, from 2002 to 2016. The number of procedures, the individual’s characteristics, characteristics of individuals, Type of malocclusion and type of surgery performed for the treatment of dentofacial deformity and / or Sleep Apnea and Obstructive Hypopnea Syndrome - OSAHS. The patients were divided into 7 groups: Maxilla (MX), Mandible (MD), Maxilla and Mandible (MX/MD); (TM), Maxilla-Mandible-Ment (MX/MD/MT); Mandible (MD/MT); (MT); Maxilla-Ment (MX/MT). The sample consisted initially of 152 patients treated in the service subdivided into two male and female groups. Both physical and electronic medical charts were evaluated and compared with data previously collected in a previous sample. Results: The present study showed that the number of orthognathic surgical treatments for the correction of deformities was significant between 2002 and 2016, and the highest incidence of surgeries occurred in the Maxilla (MX) groups, with 53.2 % of the cases, Jaw (MD), with 17.7 % of the cases and Jaw and Jaw (MX/MD), with 17.0 % of the cases, as shown qualitatively and quantitatively in table 1 and figures 3 and 4. Surgeries of maxillary advancement (MX) exclusively correspond to the largest number of the sample, representing seventy-three (74) patients, as shown in figure 4. In addition, there was a higher incidence of female surgeries with 51.0 % of the cases. In addition, there was no influence of the continuous predictor "age" and "sex" on the predictor response "orthognathic surgery", since the critical level of significance was p> 0.05. Conclusion: It was concluded that there was an increase in cases of orthognathic surgery in the last years, and with homogeneous samples between the male and female genders, and the advances in maxillary surgery were according to the greater number of surgical treatments.